From Hegemonic Masculinity to Parallel Cultures of Masculinities - Friebel, Harry (Momentum Quarterly, 2015)
The article centers the hypothesis of an increasingly problematic male role tradition as a result of socio- economic changes. The accepted range of traditional masculine behavior, whether social or private, keeps get- ting tighter throughout modernity. Multiple forms of manhood were foregrounded, replacing former fictions of natural male superiority. The new reconstruction of masculinity within gender relations is best understood, when social context and individual behavior are reflected on equally. This analysis of interaction change between social structure and personality harks back to the concept of „hegemonial masculinity“, being a mirror of normed masculinity within patriarchy. Challenges of traditional masculinity gradually liquidate the monoculture of dominant maleness. Masculinity is mooted. Behavioral alternatives as well as political equalization activities are becoming essential within social change. A gender relation between man and woman on „eye height“ is required.
Keywords: Hegemonic masculinity; crisis of manhood; „new“ men; socio-economic Change